THE EFFECT OF TECHNOLOGY PREFERENCES AND CHANGES IN CONSUMER TASTES ON CUSTOMER LOYALTY ON E-COMMERCE PLATFORMS: THE ROLE OF PURCHASE DECISIONS AS A MEDIATION VARIABLE THE EFFECT OF TECHNOLOGY PREFERENCES AND CHANGES IN CONSUMER TASTE ON CUSTOMER LOYALT - Firdaus Rofiansyah; Saida Zainurossalamia; Wirasmi Wardhani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of technology preferences and changes in consumer tastes on customer loyalty in e-commerce platforms, with purchase decision as a mediating variable. The rapid growth of e-commerce requires a comprehensive understanding of factors influencing digital consumer behavior. This research employs a quantitative approach using survey data collected from e-commerce users in Indonesia. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among variables. The results indicate that technology preferences and changes in consumer tastes significantly affect purchase decisions. Furthermore, purchase decisions significantly influence customer loyalty. In addition, purchase decisions act as a mediating variable that strengthens the relationship between technology preferences and consumer taste changes on customer loyalty. These findings suggest that customer loyalty in e-commerce is not solely determined by technological quality or social dynamics, but also by consumers' evaluative processes in making purchase decisions. This study contributes theoretically by integrating technological, social, and behavioral perspectives into a comprehensive model, and provides practical implications for developing e-commerce strategies focused on user experience and decision-making reinforcement.